1976
DOI: 10.1044/jshd.4102.216
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Perception of Time-Compressed Speech on Two Measures of Speech Discrimination

Abstract: Time-compressed versions of the WIPI and PB-K 50 speech discrimination measures were presented at two sensation levels to 60 children divided into three age-groups of 20 each. Results showed that average intelligibility scores increased as a function of increasing age and sensation level and decreased with increasing amounts of time compression. The PB-K 50 measure was found to be more difficult than the WIPI for each age-group under each condition of time compression and sensation level. The several factors u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
10
0
2

Year Published

1978
1978
2007
2007

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 0 publications
5
10
0
2
Order By: Relevance
“…Therefore, the results obtained in this study are similar to those found in the literature, 7,13,14,17 that report decreased intelligibility with the increase of time-compression, a gradual fall of the averages of correct responses at compression levels until the 60% level, and lower averages of correct responses at 70% time-compression.…”
Section: Compression) Time-compressed Speech Test In Brazilian Portusupporting
confidence: 82%
See 2 more Smart Citations
“…Therefore, the results obtained in this study are similar to those found in the literature, 7,13,14,17 that report decreased intelligibility with the increase of time-compression, a gradual fall of the averages of correct responses at compression levels until the 60% level, and lower averages of correct responses at 70% time-compression.…”
Section: Compression) Time-compressed Speech Test In Brazilian Portusupporting
confidence: 82%
“…Some factors collaborated for the lower intelligibility in the 70% timecompression, and among them was the fact that the individual has to form, test, and reject several hypotheses in the search for the correct word, which is in agreement with the findings of Friedman and Johnson; 10 additionally, participants have to be more alert and vigilant during the evaluation, since the most compressed lists present increased distortion and decreased redundancy. Katz and Wilde (1985), 12 also reported The list with highest average of correct responses was the disyllable list with 50% time-compression, which was thus the easiest list and the one with the highest degree of intelligibility.Therefore, the results obtained in this study are similar to those found in the literature, 7,13,14,17 that report decreased intelligibility with the increase of time-compression, a gradual fall of the averages of correct responses at compression levels until the 60% level, and lower averages of correct responses at 70% time-compression.In auditory training programs, the average of correct responses should be between 30% and 70% to maintain the patient's motivation, ie, so that the test is not too easy nor too difficult to the point of not maintaining a challenge to the brain. …”
supporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, all subjects obtained scores considerably poorer than those reported for normal adult listeners, whose mean score was above 90% (Beasley, Forman and Rintelmann, 1973) . The present study supports the finding (Beasley, Maki and Orchik, 1976) that time compression has a more adverse effect on intelligibility scores for children than for adults.…”
Section: Resultssupporting
confidence: 81%
“…Thus, caution should be exercised when interpreting children's discrimination scores using adult norms. Beasley, Maki and Orchik (1976) provide normative soundfield data for children age 3.5 to 8.5 on open set SO-word speech discrimination lists (PB-KSO) and closed set Word Intelligibility by Picture Identification (WIPI) material compressed at 0%, 30%, and 60%. Their data revealed that as time compression increased, word intelligibility decreased, with the poorest discrimination scores occurring at 60% compression.…”
Section: Mild Hearing Losses In Childrenmentioning
confidence: 99%